2022
DOI: 10.3389/fragi.2022.899744
|View full text |Cite|
|
Sign up to set email alerts
|

Auxin-Inducible Degron System Reveals Temporal-Spatial Roles of HSF-1 and Its Transcriptional Program in Lifespan Assurance

Abstract: HSF-1 is a key regulator of cellular proteotoxic stress response and is required for animal lifespan. In C. elegans, HSF-1 mediated heat shock response (HSR) declines sharply on the first day of adulthood, and HSF-1 was proposed to function primarily during larval stages for lifespan assurance based on studies using RNAi. The tissue requirement for HSF-1 in lifespan, however, is not well understood. Using the auxin-inducible degron (AID) system, we manage to uncouple the roles of HSF-1 in development and longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…HSF-1 is well-known for its roles in proteotoxic stress responses, such as against heat shock, but it also regulates gene expression in physiological conditions during development, reproduction, and aging ( 9, 22, 23 ). In a previous study, we identified the HSF-1 transcriptional program in C. elegans germline by combining tissue-specific HSF-1 depletion using the auxin-inducible degron (AID) system with ChIP-seq and RNA-seq analyses at ambient temperature ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…HSF-1 is well-known for its roles in proteotoxic stress responses, such as against heat shock, but it also regulates gene expression in physiological conditions during development, reproduction, and aging ( 9, 22, 23 ). In a previous study, we identified the HSF-1 transcriptional program in C. elegans germline by combining tissue-specific HSF-1 depletion using the auxin-inducible degron (AID) system with ChIP-seq and RNA-seq analyses at ambient temperature ( 9 ).…”
Section: Resultsmentioning
confidence: 99%